Impact of host restriction factors and capsid evolution on HIV disease progression - Boswell, M (2019)
HIV-1 is responsible for the global HIV pandemic whereas HIV-2 has mostly been limited to West Africa. The key to their successful spread is their unparalleled ability to adapt to the host immune system. The contemporary HIV pandemics are the latest iteration in a millennia-long evolutionary arms race between retroviruses and their hosts. Two host restriction factors which have been important actors in this arms race are TRIM5α and its paralogue TRIM22. TRIM5α targets the retroviral capsid, whereas TRIM22 suppresses retroviral transcription indirectly. The central hypothesis for the thesis is that the HIV capsid and TRIM restriction are associated with HIV disease progression. In this thesis we present findings from four projects. In chapter three we discuss the effect of TRIM genotype on disease outcomes in children and adolescents infected perinatally with HIV-1. We characterised TRIM genetic diversity in this cohort and found that TRIM22 genotype is associated with CD4+ T cell counts and, potentially, disease progression rates. Chapter four presents the outcomes of using CD4+ T cell kinetic data to stratify HIV-2 infected adults into disease progressor groups. Forty-six percent of patients were classified as fast progressors and 54% as slow progressors. Slow progressors advanced to AIDS at approximately half the rate of fast progressors, had higher CD4+ T cell levels and a slower CD4+ T cell decline rate. In chapter five we discuss the effect of TRIM genotype on HIV-2 disease outcomes in adults. TRIM22 genotype associated with significant effects on long-term CD4+ levels, though these effects were modest. Finally, we report that intrahost evolutionary rates of HIV-2 gag are significantly higher in fast progressors, that the p24 region evolves under negative selection and that evolutionary rates correlate negatively with CD4+ T cell percentage